Effect of Fortification with High-Milk-Protein Preparations on Yogurt Quality - Justyna Żulewska; Maria Baranowska; Marika Magdalena Bielecka; Aneta Zofia Dąbrowska; Justyna Tarapata; Katarzyna Kiełczewska; Adriana Łobacz (Foods)
Protein-enriched yogurts have become increasingly popular among consumers seeking to boost their daily protein intake. The incorporation of milk proteins and protein preparations in yogurt production not only enhances nutritional value but also improves texture, viscosity, and overall sensory properties—key factors that influence consumer acceptance. The main objective of this study was to evaluate the influence of casein and whey protein preparations on the physicochemical properties, viability of lactic acid bacteria, and sensory attributes of yogurts. Yogurts were enriched with 2% (w/w) protein preparations, including micellar casein preparation (CN85), whey protein isolate (WPI), whey protein concentrate (WPC60), and protein preparations obtained from skim milk by membrane filtration: micellar casein concentrate (CN75) and serum protein concentrate (SPC). The yogurts were produced using the thermostatic method, and their chemical composition, rheological properties, syneresis, firmness, lactic acid bacteria population, and sensory attributes were evaluated. The effects of high-protein preparations derived from skim milk through laboratory-scale membrane filtration processes (SPC, CN75) were compared with those of commercially available protein preparations (SMP, CN85, WPI, and WPC). Obtained results demonstrated that the membrane filtration-derived preparations (SPC and CN75) exhibited advantageous physicochemical properties and supported robust viability of yogurt and probiotic bacteria. However, their sensory quality was marginally inferior compared to the commercial preparations (SMP, CN85, WPI, and WPC). These findings indicate the potential applicability of membrane filtration-derived protein preparations in yogurt production while underscoring the necessity for further investigation to enhance and optimize their sensory characteristics.